SWOT ANALYSIS OF EASY WADI'AH SAVINGS PRODUCTS AT BANK SYARIAH INDONESIA (BSI) RADEN FATAH BRANCH BATAM - Aslina, Neri; Maggangka, Mursalin; Iqbal Azhari , Muhammad; Akmal, Randi (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2024)
This research aims to analyze the strengths, weaknesses, opportunities and threats of the Easy Wadi'ah savings product at Bank Syariah Indonesia (BSI) Raden Fatah Batam Branch. The method used in this research is SWOT analysis, which provides a comprehensive framework for evaluating various internal and external factors that influence the performance of this savings product. The analysis results show that the Easy Wadi'ah savings product has several strengths, including superiority in the sharia principles adopted, ease of access and use, and adequate technological support. However, there are also several weaknesses such as limited additional features compared to conventional products and a lack of effective promotion. Opportunities that can be exploited include increasing public awareness of sharia banking products and large market potential in the Batam area. On the other hand, the threats faced include tight competition with savings products from other banks and changes in sharia banking regulations which could affect product operations. By understanding these strengths, weaknesses, opportunities and threats, it is hoped that Bank Syariah Indonesia (BSI) Raden Fatah Batam Branch can formulate appropriate strategies to increase competitiveness and customer loyalty towards Easy Wadi'ah savings products.